FIQIH MUAMALAH SEBAGAI DASAR ETIKA BISNIS ISLAM DALAM KEGIATAN EKONOMI MODERN - Hilmi Ahsan Sutisno; Muhammad Ridlo Assyauqi; Nawal Riska Salsabila; Nurah Andini Rahmani Rizki (Taksasila Edukasi Insani, 2025)
This research seeks to explore the significance and impact of fiqh muamalah as the foundation of Islamic business ethics in addressing the challenges of the modern economy. In the dynamic world of business, principles such as honesty, justice, and social responsibility are essential for building an ethical and sustainable economic system. The research method used is a literature review with a descriptive approach, analyzing both classical and contemporary sources related to fiqh muamalah. This study highlights how Islamic values can be applied in the context of digital economics, e-commerce, fintech, and corporate social responsibility. The findings indicate that fiqh muamalah remains relevant and can serve as an ethical foundation for modern business practices. Sharia principles offer moral guidance for entrepreneurs in balancing material and spiritual aspects. Keywords : fiqh muamalah, islamic business ethics, modern economics